The Significance of Transaminases and Deritis Ratio for Predicting Alcoholic Liver Disease: A Hospital Based Comparative Study in Western Nepal - Mittal, Ankush; Sathian, Brijesh; Kumar, Arun; Chandrasekharan, Nishida; Yadav, Shambhu Kumar (Nepal Journal of Epidemiology, 2010)
Background In Nepal, alcoholic liver disease (ALD) is a major public health problem. In testing for biochemical abnormalities in ALD, Deritis ratio (AST/ALT) is more sensitive than other conventional parameters, at any stage of the disease. The aim of our study was to assess closely the significance of transaminases and deritis ratio and their predictive implications among the patients of alcoholic liver disease in Pokhara valley. Materials and Methods It was a hospital based retrospective study carried out from the data maintained in the Department of Biochemistry of the Manipal Teaching Hospital, Pokhara, Nepal between 1st January 2009 and 31st July 2010. The variables collected were age, gender, total protein, albumin, AST, ALT and AST/ALT ratio. Descriptive statistics and testing of hypothesis were used for the analysis. Data was analyzed using EPI INFO and SPSS 16 software. Results Of the four hundred forty-five patients, there was a slight preponderance of males (55.5%) towards ALD as compared to females (44.5%), projecting the percentage of ALD to around 28.8. Males were 2.3 times more at risk of developing alcoholic liver disease than females (Odds Ratio=2.3, p=0.0001). Patients over 40 years of age had 3.2 times greater propensity of developing alcoholic liver disease (Odds Ratio=3.2, p=0.0001). In ALD patients, mean value of AST (131.5 ± SD94.46 IU/L) was markedly increased in comparison to ALT (85.12 ± SD58.24 IU/L) leading to significantly higher AST/ALT ratio (1.59 ± SD0.58). In cases, mean value of Deritis ratio was 1.59 with CI (1.49, 1.69) which was significantly increased as compared to the ratio in controls which was 1.04 with CI (1.02, 1.06) (p=0.001). 96.9% of patients with alcoholic liver disease had an AST:ALT ratio of >1.0 with CI (93.9%,99.9%). The mean value of each variable in cases was significantly elevated as compared to controls (p=0.001). Conclusion Ethanol consumption leads to a spectrum of liver diseases, the importance of which is magnified by its widespread use. Laboratory tests play an important role in this endeavor. Equally important is the fact that once complications of alcoholism are identified, it is imperative to be able to accurately determine their magnitude. Therefore, the estimation of deritis ratio is useful for the rational understanding of the extent of damage in alcoholic liver disease. Key Words: Transaminase; Deritis ratio; Alcohol Liver Disease; Nepal DOI: 10.3126/nje.v1i1.4110 Nepal Journal of Epidemiology 2010;1 (1): 33-37